Reception: Covid-19 On-line Support Group Experience Report for the Bereaved - Bicalho reis, Luciana; Magalhães Gonçalves, Ana Luiza; da Silva Cajaiba, Karina; da Silva , Maiara; Rocha de Morais Fiorese , Aline; Brunetti Lambert, Carla; Augusta Magalhães Oziel , Rafaela (Guará Journal, 2025)
Reports the experience of Covid-19 bereaved online Support Groups. 10 weekly meetings were held, with 8 participants. With a brief and focal approach, it aimed to help the bereaved to resolve separation conflicts and facilitate the adaptation to grief. The activities were designed based on the demands of the group and its characteristics. From the participants’ reports, it was noticed that the support group constituted an importantspace for the expression and validation of the emotions and feelings that make up the experience of grief, with the possibility of learning about grief and the construction of social support networks and emotional. In the pandemic, risk factors increase for more difficult experiences of mourning, such as multiple losses, lack of social support and absence of traditional farewell rituals. Proposals such as Acolhe(dor) can reduce the risks forcomplicated grief and produce positive effects on the mental health of the bereaved.
Keywords: Bereavement; Self-help groups; Psychosocial intervention; Covid-19